Upaya Program Kampung Iklim Dalam Pengelolaan Sampah Untuk Mengurangi Sumber Emisi GRK - Ismike Suci; Nurhasan Syah; Robiyati Robiyati (Dinamika Lingkungan Indonesia, 2024)
The Climate Village Program (called ProKlim, Program Kampung Iklim, in Indonesian language) is the main center to guide various parties in carrying out their roles in improving solid and liquid waste management actions as one of the pillars of ProKlim activities. Waste is one of the sectors that contributes to increasing greenhouse gas (GHG) emissions. The activities carried out by the community at the ProKlim location, including waste management, is a concrete example of the implementation of climate change adaptation and mitigation. This study aims to analyze efforts to implement the Climate Village Program Efforts in Waste Management to reduce sources of GHG emissions. This research applied descriptive qualitative method. Data collection techniques used documentation studies and interviews with purposive sampling technique, as well as data collection analysis techniques, data reduction, display data, and conclusion. The researchers draw conclusions and verifies the data. The results showed that the efforts such implementing the 3R program (implementing zero waste; reuse, reduce, recycle) in waste management, household composting and adding vegetation cover in the Climate Village Program in managing waste has potential to minimize the impact of greenhouse gas emissions (GHG).